(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Body stalk anomalies are a group of massively disfiguring abdominal wall defects in which the abdominal organs lie outside of the abdominal cavity in a sac of amnioperitoneum with absence of or very small umbilical cord. Various hypotheses proposed to explain the pathogenesis of limb body wall complex include early amnion disruptions, embryonic dysplasia, and vascular disruption in early pregnancy. Body stalk anomaly is an accepted fatal anomaly and, hence, its early diagnosis aids in proper management of the patient. We present a case of LBWC, exhibiting combined cranial, abdominal & limb features. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 56-58